Atypical centrioles during sexual reproduction - Avidor-Reiss, Tomer; Khire, Atul; Fishman, Emily L.; Jo, Kyoung H. (Frontiers in Cell and Developmental Biology, 2015)
Centrioles are conserved, self-replicating, microtubule-based 9-fold symmetric subcellular organelles that are essential for proper cell division and function. Most cells have two centrioles and maintaining this number of centrioles is important for animal development and physiology. However, how animals gain their first two centrioles during reproduction is only partially understood. It is well established that in most animals, the centrioles are contributed to the zygote by the sperm. However, in humans and many animals, the sperm centrioles are modified in their structure and protein composition, or they appear to be missing altogether. In these animals, the origin of the first centrioles is not clear. Here, we review various hypotheses on how centrioles are gained during reproduction and describe specialized functions of the zygotic centrioles. In particular, we discuss a new and atypical centriole found in sperm and zygote, the proximal centriole-like structure (PCL). We also discuss another type of atypical centriole, the “zombie” centriole, which is degenerated but functional. Together, the presence of centrioles, PCL, and zombie centrioles suggests a universal mechanism of centriole inheritance among animals and new causes of infertility. Since the atypical centrioles of sperm and zygote share similar functions with typical centrioles in somatic cells, they can provide unmatched insight into centriole biology.